(untitled) (Damascus University Journal of arts and humanities sciences, 2022)
Digital medialiteracy is a renewed topic in modern society, and it attracts the attention of specialists in the fields of media, communication and education. It is considered a completely new field in the Syrian society. Therefore, this research examined the relationship of the digital media audience to the standards and dimensions of digital media literacyin a survey applied study on 160 high school students in Damascus. The importance of the study stems from its being the first research to study the topic of digital media literacy, especially the Syrian public’s relationship with it. As for the research objectives, they are summarized by identifying the importance of digital media literacy, and to identify the extent to which students’ media and communication practices are compatible with the standards and dimensions of digital media literacy. The most prominent results of the research indicated that students’ use of digital technologies and means and their digital media and communication practices are poorly compatible with the four academic standards for digital media literacy, and that students ’possession and use of technologies and methods and their digital media and communication practices correspond to medium degrees with the six dimensions of digital media literacy, and that the level of students’ awareness for digital media literacy, the level of their commitment to its principles ranges from weak to medium degrees. Therefore, it is necessary for students to learn digital media and communication literacy skills through a scientific subject or a digital media literacy course, or integrating digital media literacy into the curriculum or study plan.